DEEP VEIN THROMBOSIS AND RECURENT PULMONARY EMBOLISM IN A PATIENT WITH THROMBOPHILIC MUTATIONS AND GENERALIZED PSORIASIS: A CASE REPORT - Baloski, Marjan; Buklioska Ilievska, Daniela; Brishkoska Boshkovski, Vesna; Hasan, Taner; Nedeska Minova, Natasha; Prgova-Veljanova, Biljana; Nanceva Bogoevska, Andrea; Nancheva, Jasminka; Bosevski, Marijan; Panov, Saso (Association of medical doctors "Sanamed" Novi Pazar, 2020)
Introduction: Genetic risk factors that increase venous thromboembolism risk are disorders in the synthesis or activity of coagulation factors. Fac- tor V Leiden, prothrombin (20210-A), antithrombin deficiency, protein C and protein S deficiency, and hyperhomocysteinaemia are the most common venous thromboembolism-related gene mutations. When ge- netic factors are combined with non-provoking risk factors (obesity, psoriasis, smoking and previous veno- us thromboembolism) the result is increased venous thromboembolism risk for each factor individually. Previous venous thromboembolism is one of the stron- gest risk factors, even in patients actively treated with anticoagulant. Patients are more likely to have recur- rent venous thromboembolism with longer duration. Psoriasis is a complex immune–mediated disease, as- sociated with cardiovascular risk, hypercoagulability markers and elevated homocysteine. Lots of observati- onal reports suggest increased incidence of venous trombembolic events in patient with psoriasis
Keywords: recurrent venous thromboembolism; thrombophilia; psoriasis; pulmonary embolism